Improving the Educational Process in Umutayyad Schools on the Basis of Cooperation (Eurasian Research Bulletin, 2022)
Cooperative teaching pedagogy is based on improving the pedagogical process and focusing it on the personality of the student. This technology serves to create a creative environment aimed at the formation of a creative personality, to increase the quality and efficiency of education. Collaborative teaching includes the main processes of training: collaborative exchange of ideas, conversation, analysis, discussion, negotiation, performance of practical tasks, problem solving. The article describes the history of the development of cooperative pedagogy, its role in the teaching process, and opinions based on the experience